2006
DOI: 10.1007/s11469-006-9033-9
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Behavior of Juvenile Offenders in Louisiana

Abstract: The purpose of this paper was to determine the (1) frequency of and (2) types of prearrest gambling (3) prevalence of pathological gambling and (4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…Not only are the current findings of a positive association between problem gambling and arrest among youth consistent with past studies, these findings also are consistent with various crime theories and the problem behavior theory . Problem gamblers, marked by an increased pressure by gambling debts, the compulsive need to continue gambling, and distorted cognitive processes resulting in faulty beliefs of personal skill and probability of winning, could be limited in their ability to rationally weigh the perceived costs and benefits of committing a crime, and thus increase their likelihood of arrest.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Not only are the current findings of a positive association between problem gambling and arrest among youth consistent with past studies, these findings also are consistent with various crime theories and the problem behavior theory . Problem gamblers, marked by an increased pressure by gambling debts, the compulsive need to continue gambling, and distorted cognitive processes resulting in faulty beliefs of personal skill and probability of winning, could be limited in their ability to rationally weigh the perceived costs and benefits of committing a crime, and thus increase their likelihood of arrest.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been reported in US adolescent populations, where higher frequencies of both gambling and gambling‐related arrests were observed in offender populations than in school samples . Westphal and Johnson compared a group of offenders with a random sample of public school students aged 10–19 years, and found that the prevalence of probable pathological gambling was five times greater in the group of offenders than among the public school students . Other risk factors that may lead juvenile gamblers to commit criminal activities include peer pressure, presence of deviant peers, and needs for financial resources to support gambling activities or to pay gambling debts .…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations